Substituted Azabicyclo[2.2.1]heptanes as Selective Orexin-1 Antagonists: Discovery of JNJ-54717793 - Préville, Cathy (ACS Med Chem Lett, 2020)
[Image: see text] The orexin system consists of two neuropeptides (orexin-A and orexin-B) that exert their mode of action on two receptors (orexin-1 and orexin-2). While the role of the orexin-2 receptor is established as an important modulator of sleep wake states, the role of the orexin-1 receptor is believed to play a role in addiction, panic, or anxiety. In this manuscript, we describe the optimization of a nonselective substituted azabicyclo[2.2.1]heptane dual orexin receptor antagonist (DORA) into orally bioavailable, brain penetrating, selective orexin-1 receptor (OX1R) antagonists. This resulted in the discovery of our first candidate for clinical development, JNJ-54717793.